Identification and analysis of type 2 diabetes-mellitus-associated autophagy-related genes - Cui, Kun; Li, Zhizheng (Frontiers in Endocrinology, 2023)
Autophagy is an important innate safeguard mechanism for protecting the organism against harmful agents. Autophagy has also been implicated in pathophysiology of type 2 diabetes mellitus (T2DM). However, the exact mechanism is unknown. The GSE25724 dataset was downloaded from the GEO database. Differentially expressed genes (DEGs) were identified in T2DM islets and non-diabetic islets samples. The differentially expressed autophagy-related genes (DEARGs) were screed by R software. Then, the DEARGs were subjected to the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO) enrichment analyses. A protein-protein interaction (PPI) network was constructed to identify hub DEARGs. Expressions of top six DEARGs were validated in pancreatic β-cells by qRT-PCR. In total, 1270 DEGs (266 up-regulated and 1004 down-regulated genes) and 30 DEARGs were discovered. The DEARGs were enriched in autophagy-and mitophagy-related terms. The PPI network showed interactions between the DEARGs. In addition, we identified GAPDH, ITPR1, EIF2AK3, FOXO3, HSPA5, RB1CC1, LAMP2, GABARAPL2, RAB7A and WIPI1 genes as the hub ARGs. Finally, qRT-PCR analysis revealed that expressions of EIF2AK3, FOXO3, HSPA5, RB1CC1, LAMP2, GABARAPL2 and RAB7A were consistent with findings from bioinformatics analysis. EIF2AK3, FOXO3, HSPA5, RB1CC1, LAMP2, GABARAPL2 and RAB7A have been identified as hub ARGs and these ARGs may T2DM development by regulating autophagy. These findings elucidate on T2DM and might as possible treatment targets for T2DM.